The Effect Of Social Capital On Interest In Entrepreneurship With Self-Efficiency - andarweni astuti; Puji Hardati (Universitas Veteran Bangun Nusantara, 2022)
The formulation of the problem in this study is how the influence of social capital on the interest in entrepreneurship with self-efficacy in STPKat students. This study aims to analyze the effect of student social capital on entrepreneurial interest with self-efficacy. In order to answer this problem, Bourdie's theory of social capital and Bandura's theory of self-affication are used. This research method is quantitative, with a focus on analyzing the influence of student social capital on the interest in entrepreneurship with self-efficacy. The analysis used in this research is simple linear regression analysis, looking for the effect of social capital variable (X) on entrepreneurial interest and self-efficacy (Y). The results obtained are social capital has a positive influence coefficient, 0.355 the higher the social capital of a student, the higher the self-efficacy, or an increase of 35.5%. Social capital has a significance t of 0.540, which means this significance is > 0.05, so social capital has no significant effect on entrepreneurial interest and self-efficacy in STPKat Semarang students. Test the coefficient of determination on the adjusted R Square value. the contribution of social capital (independent variable) 8.8% to self-efficacy, in the sense that 81.2% can be found in further research outside the social capital variable.